Identifying fake news through trustworthiness judgements of documents / La identificación de noticias falsas mediante juicios de fiabilidad de los documentos. Issue 2 (3rd April 2019) - Tarchi, Christian
Abstract: In the twenty-first century, people have access to a great wealth of knowledge to solve information-based problems. However, sources might include misinformation, a phenomenon also called 'fake news'. In this study, the contribution of students' affective engagement and behaviour disposition on Italian university students' multiple-document comprehension will be investigated. In specific, the focus was put on trustworthiness judgements and use of justification criteria when reading documents on the controversial topic of vaccination. Participants were 289 university students. The procedure included four steps. Firstly, students were administered the tests measuring prior beliefs, topic interest and prior knowledge. Secondly, students read six documents varying by position towards vaccination and reliability. Thirdly, students were asked to report their use of processing strategies. Finally, students were asked to judge the trustworthiness of the six documents and report to what extent they had relied on specific trustworthiness criteria. Overall results confirmed the existence of four default stances adopted to complete the reading task, which are significantly associated with trustworthiness judgements. Students' affective engagement should be targeted by enhancing their topic interest, and intervention should promote cross-document strategic processing.